KLF4 and CD55 expression and function depend on each other - An, Feng-Qi; Zhou, Guangjin; Harland, Micah T.; Hussain, Wasim; Strainic, Michael G.; Jain, Mukesh K.; Medof, M. Edward (Frontiers in Immunology, 2024)
The transcription factor Kruppel-like factor 4 (KLF4) regulates the expression of immunosuppressive and anti-thrombotic proteins. Despite its importance in maintaining homeostasis, the signals that control its expression and the mechanism of its transactivation remain unclarified. CD55 [aka decay accelerating factor (DAF)], now known to be a regulator of T and B cell responses, biases between pro-and anti-inflammatory processes by controlling autocrine C3a and C5a receptor (C3ar1/C5ar1) signaling in cells. The similarity in CD55's and KLF4's regulatory effects prompted analyses of their functional relationship. In vascular endothelial cells (ECs), CD55 upregulation accompanied KLF4 expression via a p-CREB and CREB Binding Protein (CBP) mechanism. In both ECs and macrophages, CD55 expression was essential for KLF4's downregulation of pro-inflammatory/pro-coagulant proteins and upregulation of homeostatic proteins. Mechanistic studies showed that upregulation of KLF4 upregulated CD55. The upregulated CD55 in turn enabled the recruitment of p-CREB and CBP to KLF4 needed for its transcription. Activation of adenylyl cyclase resulting from repression of autocrine C3ar1/C5ar1 signaling by upregulated CD55 concurrently led to p-CREB and CBP recruitment to KLF4-regulated genes, thereby conferring KLF4's transactivation. Accordingly, silencing CD55 in statin-treated HUVEC disabled CBP transfer from the E-selectin to the eNOS promoter. Importantly, silencing CD55 downregulated KLF4's expression. It did the same in untreated HUVEC transitioning from KLF4 low growth to KLF4 hi contact inhibition. KLF4's and CD55's function in ECs and macrophages thus are linked via a novel mechanism of gene transactivation. Because the two proteins are co-expressed in many cell types, CD55's activity may be broadly tied to KLF4's immunosuppressive and antithrombotic activities.